New species of the genus Archimonocelis Meixner, 1938 (Proseriata, Archimonocelididae) from southern Apulia (Italy) - Curini-Galletti, Marco; Delogu, Valentina; Campus, Paolo; Casu, Marco (Zootaxa, 2007)
A survey of the composition of the genus Archimonocelis Meixner, 1938 in southern Apulia (Italy) revealed the presence of four species, three of which are new. Archimonocelis scopulicola n. sp. has a straight stylet, provided with a girdle of 18 copulatory spines, and a chromosome set with n=10. In both A. cygnicollis n. sp. and A. parastaresoi n. sp., an accessory glandular organ, provided with spines, is present. A. cygnicollis n. sp. is provided with a unique double-walled stylet. A. parastaresoi n. sp. is similar to the western Mediterranean A. staresoi Martens & Curini-Galletti, 1993; size and shape of accessory spines are the main discriminating features between the two species. In addition, numerous specimens of A. carmelitana Martens & Curini-Galletti, 1993 were found. A comprehensive discussion of the new species is given.